EVALUASI PENDIDIKAN INKLUSIF DI SEKOLAH DASAR DI WILAYAH II KECAMATAN KEBAYORAN BARU - Maulana Yusuf; Anna Suhaenah Suparno; Purnama Syaepurohman (Prosiding Seminar Nasional Berseri, 2020)
This study aims at evaluating the inclusive education policies in Elementary Schools in Region II of Kebayoran Baru district, including (1) conformity with the implementation of inclusive education with eight National Education Standards (2) describe various obstacles in the implementation of inclusive education, and (3) solutions that can be done to overcome obstacles when implementing inclusive education. This research is an evaluation study using the Discrepancy model approach. The results of this study indicate that (1) the implementation of inclusive education policies in Primary Schools is not yet in line with the minimum service standards of inclusive education, which covers the eight National Standards of Education with the achievement rates of 40.34% in the poor category, and a gap of 59.66% (2) the obstacles faced were the absence of Special Advisory Teachers and the lack of regular teacher understanding of inclusive education, inadequate facilities and infrastructure for special students, and (3) solution that can be done to overcome these obstacles is to provide elaboration, provide training for regular teachers about inclusive education , and collaborating with related parties in order to implement the inclusive education.